Calix[n]arenes: active organocatalysts for the synthesis of densely functionalized piperidines by one-pot multicomponent procedure. Issue 19 (11th May 2016) - Palermo, V.; Sathicq, A.; Liberto, N.; Fernandes, S.; Langer, P.; Jios, J.; Romanelli, G.
Graphical abstract: Highlights: An efficient methodology for the synthesis of heavily functionalized piperidines. A pseudo-five component, one-pot domino reaction using p -sulfonic acid calix[ n ]arenes. Eco-friendly protocol with atomic economy and short reaction time from simple materials. The organocatalyst can be recycled without reduction of its catalytic activity. Abstract: An efficient, suitable and high yielding method has been developed for the synthesis of different densely functionalized piperidine derivatives via pseudo-five component, one-pot domino reaction through a combination of β-ketoesters, aromatic aldehydes, and various amines using p -sulfonic acid calix[ n ]arenes as catalysts. The reaction was carried out in refluxing methanol, affording very good yields of the expected piperidine. Atomic economy, environmentally benign procedure, reuse of catalysts, and short reaction time are some of the important features of this protocol.